In vitro glucocorticoid sensitivity is associated with clinical glucocorticoid therapy outcome in rheumatoid arthritis - Quax, Rogier AM (BioMed Central, 2012)
INTRODUCTION: Genetic and disease-related factors give rise to a wide spectrum of glucocorticoid (GC) sensitivity in rheumatoid arthritis (RA). In clinical practice, GC treatment is not adapted to these differences in GC sensitivity. In vitro assessment of GC sensitivity before the start of therapy could allow more individualized GC therapy. The aim of the study was to investigate the association between in vitro and in vivo GC sensitivity in RA. METHODS: Thirty-eight early and 37 established RA patients were prospectively studied. In vitro GC sensitivity was assessed with dexamethasone-induced effects on interleukin-2 (IL-2) and glucocorticoid-induced leucine zipper (GILZ) messenger RNA expression in peripheral blood mononuclear cells (PBMCs). A whole-cell dexamethasone-binding assay was used to measure number and affinity (1/K(D)) of glucocorticoid receptors (GRs). In vivo GC sensitivity was determined by measuring the disease activity score (DAS) and health assessment questionnaire disability index (HAQ-DI) score before and after 2 weeks of standardized GC treatment. RESULTS: GR number was positively correlated with improvement in DAS. IL-2-EC(50 )and GILZ-EC(50 )values both had weak near-significant correlations with clinical improvement in DAS in intramuscularly treated patients only. HAQ responders had lower GILZ-EC(50 )values and higher GR number and K(D). CONCLUSIONS: Baseline cellular in vitro glucocorticoid sensitivity is modestly associated with in vivo improvement in DAS and HAQ-DI score after GC bridging therapy in RA. Further studies are needed to evaluate whether in vitro GC sensitivity may support the development of tailor-made GC therapy in RA.